2015
DOI: 10.5539/ijef.v7n7p74
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Sustainability Performance and Stock Market Returns: An Empirical Analysis of the Dow Jones Sustainability Index Europe

Abstract: This paper investigates the relation between corporate financial performance (CFP) and corporate sustainability performance (CSP). This is done by first analyzing a sample of European stocks that were added to or deleted from the Dow Jones Sustainability Europe Index (DJSI Europe) over the period [2009][2010][2011][2012][2013], and second by analyzing a sample of European stocks that were recognized as industry group leaders in CSP by the DJSI Europe over the same period. The impacts are measured in terms of (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
(47 reference statements)
2
16
0
3
Order By: Relevance
“…Therefore, we found a positive relation between the CSR index (on one hand) and equity and market capitalization (on the other hand). We also identified the existence of a positive relation between the CSR index and return on equity and return on assets, as it was previously found for other countries (Jiang and Yang, 2015;Stekelenburg et al, 2015;Choi, Kwak and Chongwoo, 2010). The obtained results confirmed the considered hypothesis, according to which there is a positive relation between measures associated to the transition towards the bio-economy concept, by implementing CSR principles, and some indicators of financial and economic performance (such as return on assets and return on equity).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Therefore, we found a positive relation between the CSR index (on one hand) and equity and market capitalization (on the other hand). We also identified the existence of a positive relation between the CSR index and return on equity and return on assets, as it was previously found for other countries (Jiang and Yang, 2015;Stekelenburg et al, 2015;Choi, Kwak and Chongwoo, 2010). The obtained results confirmed the considered hypothesis, according to which there is a positive relation between measures associated to the transition towards the bio-economy concept, by implementing CSR principles, and some indicators of financial and economic performance (such as return on assets and return on equity).…”
Section: Discussionsupporting
confidence: 77%
“…In order to estimate the impact induced by measures adopted for implementation of CSR concept on the financial performance of the analysed companies, we considered CSR variable as being independent variable, in panel data regression models, where the dependent variable is different measures of financial performance. The choice for this model was made considering some other studies, such as Jiang and Yang, 2015;Stekelenburg et al, 2015;Choi, Kwak and Chongwoo 2010;Orlitzky, 2001;Dumitrescu and Simionescu, 2015. In order to verify H3 hypothesis, in table no. 4 are presented the results for a regression model where the dependent variable is ROE and the independent variables are CSR index, logarithmic values for total assets and market capitalization, sales growth and average number of employees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Stekelenburg et al [27] examined the link between financial performance and CS performance by analyzing a sample of European stocks included to or deleted from the DJ Sustainability Europe Index over the period 2009-2013. They found that adding to the index temporarily increases the stock price for one trading day after the announcement, and removal from the index temporarily decreases the stock price for between five and ten trading days after the effective change date.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Meanwhile, Garcia-Castro, Arino, and Canela (2010) proposed a negatively effect CSP on CFP. Stekelenburg, Georgakopoulos, Sotiropoulou, Vasileiou, and Vlachos (2015) explained the relationship between CFP and CSP by using the resource view of stakeholder theory. According to this theory, firms that invest in CSP have superior resources.…”
Section: Introductionmentioning
confidence: 99%